The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s0103-90162007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Improving predictions of leaf appearance in field grown potato

Abstract: The calculation of leaf appearance rate (LAR) and number of accumulated or emerged leaves (NL) on the main stem are part of many crop simulation models. The purpose of this study was to adapt and evaluate a model (WE model) for simulating the main stem LAR and NL in potato (Solanum tuberosum L.). The WE model is a non-linear multiplicative model that takes into account the effect of genotype and environmental factors on LAR. A linear model (Phyllochron model) was also used as a comparison with the WE model. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(39 reference statements)
1
9
0
3
Order By: Relevance
“…These results are in agreement with STRECK et al (2006) who found that tuber initiation in potato is delayed in elevated temperature scenarios during the fall growing season, whereas tuber initiation was hastened during the spring growing season. Results also agree with observed results by STRECK et al (2007) that leaf appearance in potato grown during summer months in Subtropical climate was delayed compared to potato grown in the spring.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in agreement with STRECK et al (2006) who found that tuber initiation in potato is delayed in elevated temperature scenarios during the fall growing season, whereas tuber initiation was hastened during the spring growing season. Results also agree with observed results by STRECK et al (2007) that leaf appearance in potato grown during summer months in Subtropical climate was delayed compared to potato grown in the spring.…”
Section: Resultssupporting
confidence: 92%
“…LN= Σ LAR, from crop emergence to the appearance of the flag leaf. The WE model was calibrated and tested previously in Rio Grande do Sul conditions (STRECK et al, 2007), and the coefficients LAR max , T min , T opt and T max are genotype-specific. In this study we used the coefficients for Asterix, a cultivar widely used by potato growers in the State of Rio Grande do Sul: LAR max = 0.872 leaves day -1 , T min =7 ºC, T opt =21 ºC, and T max =30 ºC (STRECK et al, 2007).…”
Section: Thismentioning
confidence: 99%
See 2 more Smart Citations
“…Na determinação do coeficiente TAF máx do modelo de WE, foram estimadas equações de regressão não-linear múltipla para os valores do NF acumulado em função dos valores acumulados de f(T). A equação de regressão forneceu o valor do coeficiente TAF máx baseado no menor valor do quadrado médio do erro (QME) (Streck et al, 2006(Streck et al, , 2007. O valor do coeficiente TAF máx para E. grandis foi de 0,4107 folhas por dia e para E. saligna foi de 0,3180 folhas por dia.…”
Section: Methodsunclassified